Gulliver's Travels - "Swift, Jonathan" (Maqbool books: Lahore, 2012)
Jonathan Swift's Gulliver's Travels is a seminal work of satirical fiction that critiques the follies and vices of human society through the fantastical voyages of Lemuel Gulliver. The novel explores themes of power, pride, morality, and the limits of human reason by juxtaposing Gulliver's experiences in diverse and exaggerated cultures. Each voyage serves as a lens to scrutinize various aspects of 18th-century European society, including politics, science, and human behaviour. A blend of adventure, fantasy, and sharp social commentary, Gulliver's Travels remains a timeless reflection on the complexities of human nature and civilization.
Keywords: English & Old English literatures